Māori women, health care, and contemporary realities : a critical reflection : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy (Health) at Massey University, Wellington, New Zealand - Parton, Beverley May (Massey University, 2015)
𝘔𝘢̄𝘰𝘳𝘪 𝘸𝘰𝘮𝘦𝘯, 𝘩𝘦𝘢𝘭𝘵𝘩 𝘤𝘢𝘳𝘦 𝘢𝘯𝘥 𝘤𝘰𝘯𝘵𝘦𝘮𝘱𝘰𝘳𝘢𝘳𝘺 𝘳𝘦𝘢𝘭𝘪𝘵𝘪𝘦𝘴 is a critical reflection on the context of my nursing practice, a Pākehā nurse employed by Kokiri Marae Health and Social Services (KMHSS), Lower Hutt, Aotearoa New Zealand. In addressing the disparities Māori experience KMHSS has the motto, “Committed to the holistic development of whānau, hapū, and iwi”. The research aimed to explore from the experiences of urban Māori women, influences on their health and health care engagement. Kawa Whakaruruhau, the critical nursing theory of cultural safety for Māori health care, informs a qualitative approach, a human rights perspective, with its categories of difference, power, and subjective assessment. In turn, whiteness theory, with its categories of white (and not so white) power and privilege, informs Kawa Whakaruruhau. The women’s stories were received in an unstructured interview method and analysed thematically. The historical, social, cultural, economic, political, racial and gendered factors contributing to Māori women’s health and health care engagement are presented as a geography of health, and as landscapes past, present and future. Landscapes past tell of the disruption of the whakapapa connections of land, language and health by the historical and ongoing processes of colonisation. Landscapes present tell of health care places and spaces that by their policies, cultures, structures, and health professional practice, network and connect to include or to exclude Māori women and their families. Landscapes future are envisioned by the women as they remember what is and has been, and then imagine for themselves and at times succeeding generations, what they require as Indigenous to be central to health care. The women imagine what they need to parent for their children to have a good life; they imagine a therapeutic landscape. (In)authentic identities are presented as chronicities of risk, inhabiting disease and poverty. The women expressed authentic mana wāhine identity uniquely and heterogeneously. Recommendations have been made for nursing practice, research site and research.
Keywords: Women, Maori; Medical care; New Zealand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Health and medical services in society